A Healable and Mechanically Enhanced Composite with Segregated Conductive Network Structure for High-Efficient Electromagnetic Interference Shielding - Wang, Ting; Kong, Wei‑Wei; Yu, Wan‑Cheng; Gao, Jie‑Feng; Dai, Kun; Yan, Ding‑Xiang; Li, Zhong‑Ming (Nano-Micro Letters, 2021)
It is still challenging for conductive polymer composite-based electromagnetic interference (EMI) shielding materials to achieve long-term stability while maintaining high EMI shielding effectiveness (EMI SE), especially undergoing external mechanical stimuli, such as scratches or large deformations. Herein, an electrostatic assembly strategy is adopted to design a healable and segregated carbon nanotube (CNT)/graphene oxide (GO)/polyurethane (PU) composite with excellent and reliable EMI SE, even bearing complex mechanical condition. The negatively charged CNT/GO hybrid is facilely adsorbed on the surface of positively charged PU microsphere to motivate formation of segregated conductive networks in CNT/GO/PU composite, establishing a high EMI SE of 52.7 dB at only 10 wt% CNT/GO loading. The Diels–Alder bonds in PU microsphere endow the CNT/GO/PU composite suffering three cutting/healing cycles with EMI SE retention up to 90%. Additionally, the electrostatic attraction between CNT/GO hybrid and PU microsphere helps to strong interfacial bonding in the composite, resulting in high tensile strength of 43.1 MPa and elongation at break of 626%. The healing efficiency of elongation at break achieves 95% when the composite endured three cutting/healing cycles. This work demonstrates a novel strategy for developing segregated EMI shielding composite with healable features and excellent mechanical performance and shows great potential in the durable and high precision electrical instruments. Highlights: 1 The cationic waterborne polyurethanes microspheres with Diels-Alder bonds were synthesized for the first time. 2 The electrostatic attraction not only endows the composite with segregated structure to gain high electromagnetic-interference shielding effectiveness, but also greatly enhances mechanical properties. 3 Efficient healing property was realized under heating environment.